Antimicrobial peptides activity in the skin. Issue 2 (15th October 2018) - Herman, Anna; Herman, Andrzej P.
Abstract: This review presents the current state of knowledge regarding multifunctional role of human skin antimicrobial peptides (AMPs), including (a) protection from microbial infection, (b) improvement of skin barrier homoeostasis, (c) modulation of inflammation responses, and (d) promotion of wound healing. In addition, association of AMPs with skin diseases as well as challenges and future prospects for AMP therapeutics has also been discussed.